2015
DOI: 10.4028/www.scientific.net/kem.669.110
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Aluminum Alloys Melting Temperature in High Pressure Casting

Abstract: The high pressure casting process is a well-established way for the manufacture of non-ferrous components. Temperature is important technological parameter of production that affects the structure and quality of castings. Using continual exact measurement of alloy temperature is the best approach for predicting structures quality problems.Temperature measurement system also would help to acquire feedback from the manufacturing process so as to prevent possible defects in next phases of manufacturing. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Therefore, from the mentioned preview it is clear that both the hardware and software precision of the wire lead, the process parameters and the heat load, considerably affect the final quality of the machined surface after WEDM in terms of its geometrical accuracy [17]. At the same time, the geometrical accuracy of the machined surface in combination with the mentioned WEDM parameters are also influenced by the structure [18,19] and chemical composition of the wire electrode [20]. However, because of the relatively complex problems in the given area, there is a lack of comprehensive and exact description of the influence of mechanical, physical and chemical properties of the wire electrode material and the machined material, as well as the WEDM process parameters, on the quality of the machined surface in terms of geometrical accuracy [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, from the mentioned preview it is clear that both the hardware and software precision of the wire lead, the process parameters and the heat load, considerably affect the final quality of the machined surface after WEDM in terms of its geometrical accuracy [17]. At the same time, the geometrical accuracy of the machined surface in combination with the mentioned WEDM parameters are also influenced by the structure [18,19] and chemical composition of the wire electrode [20]. However, because of the relatively complex problems in the given area, there is a lack of comprehensive and exact description of the influence of mechanical, physical and chemical properties of the wire electrode material and the machined material, as well as the WEDM process parameters, on the quality of the machined surface in terms of geometrical accuracy [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…From this overview of basic operating factors it can be concluded that substantial negative impact on the geometric accuracy of the machined surface after WEDM has insufficient kinematic precision of electro-erosion machines, low precision of mechanical lead [20], management software errors of wire electrodes [21], but also an unsuitable combination of process parameter settings. Tab.…”
Section: Geometric Deviations Of the Shape Of Machined Surface After ...mentioning
confidence: 99%
“…without any problems and at the same time create complicated shapes. [2] This is mainly due to the use of physical or physicochemical principles of material removal. All of the above-mentioned special applications of available manufacturing technologies include the production of die casting moulds [1].…”
Section: Introductionmentioning
confidence: 99%